La Batalla de Orgreave. Entre el simulacro, el teatro de masas y el cine político - Ferrero, Ángel (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The article issues some of the questions posed by modern aesthetics like the historicity in the works of art and the depiction of social and political conflicts and its consequences in the social discourse, from the recreation of the Battle of Orgreave staged by british artist Jeremy Deller for the London-based art-center Artangel to the films of Serguei M. Eisenstein and Peter Watkins and the theater of Erwin Piscator and Rimini Protokoll.